ADVERSE DRUG INTERACTION BETWEEN ASPIRIN AND FUROSEMIDE: A CASE REPORT: A CASE REPORT - GUNDETI KAVYA REDDY,; NISI GRACE KURIAKOSE, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Drug–drug interaction between two drugs leads to a serious adverse drug reaction which is an adverse drug interaction. A 60-year-old female patient came with complaints of chest pain since 6 pm on the day of admission which is a burning type of pain and also a history of breathlessness. She was a known case of hypertension and diabetes mellitus since 5 years on medications, i.e. tablet atenolol-5 mg - 1-0-0, tablet amlodipine - 5 mg - 1-0-0, and tablet metformin - 500 mg - 1-0-1; the patient’s appetite was reduced and sleep was disturbed. On examination, blood pressure was 120/100 mmHg, pulse rate: 80 bpm, SpO2: 94% with room air, respiratory system: B/L coarse crept (+), and pallor (+) remaining systemic examination showing no any deformities. Laboratory reports show microcytic hypochromic with neutrophilia and thrombocytosis and ultrasonography (USG): B/L Grade I renal parenchymal disease. The patient ongoing treatment was tablet aspirin - 325 mg stat and 150 mg 0-1-0, tablet clopidogrel 300 mg stat and 75 mg 0-1-0, tablet atorvastatin 80 mg stat and 40 mg 0-0- 1, injection furosemide 40 mg IV 1-1-0, and injection nitroglycerin 2 amp in 1 pint NS at 12 drops/min and stopped on the 2nd day; injection pantoprazole 40 mg IV 1-0-1, injection heparin 5000 IU IV 1-1-1, and injection insulin R 8-8-6 S/C 1-0-1 started from the 2nd day; tablet enalapril 2.5 mg PO 1-0-1 given on the 2nd and 3rd days; tablet amlodipine 5 mg PO 1-0-1 given on the 2nd day and stopped; and injection insulin 1 pint in 25% dextrose, injection calcium gluconate, and nebulizer asthalin given only on the 3rd day. Here come 6 major interactions between amlodipine and clopidogrel, aspirin and furosemide (causes possible nephrotoxicity), clopidogrel with aspirin and heparin (increased risk of bleeding) and also heparin with nitroglycerin. The patient diagnosed as chronic kidney disease in the middle of the treatment which was adverse reaction interaction between aspirin and furosemide.